2015
DOI: 10.1517/17425255.2015.1052404
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of dendrimer prodrugs

Abstract: Drug-dendrimer conjugates are preferable to drug-dendrimer complexes, where the use of degradable linkers is critical to the release of the drug. Polyethylene glycol and/or ligands can be added to a dendrimer prodrug, which is useful for the targeting of affected tissues. Imaging probes can also be incorporated into dendrimer prodrugs for the simultaneous delivery of therapeutic and diagnostic agents as 'theranostics.'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Moreover, one study compared the PAMAM dendrimers’ suitability with DOTAP liposomes for topical delivery of siRNA against TNF-α. The results showed that phenotypic and histopathological features were improved, and IL-6, TNF-α, IL-17, and IL-22 levels decreased in the dendritic plexus and liposome treatment groups compared to the imiquimod group ( 58 ).…”
Section: Promising Strategies: Advanced Topical Nanocarrier Systemsmentioning
confidence: 98%
“…Moreover, one study compared the PAMAM dendrimers’ suitability with DOTAP liposomes for topical delivery of siRNA against TNF-α. The results showed that phenotypic and histopathological features were improved, and IL-6, TNF-α, IL-17, and IL-22 levels decreased in the dendritic plexus and liposome treatment groups compared to the imiquimod group ( 58 ).…”
Section: Promising Strategies: Advanced Topical Nanocarrier Systemsmentioning
confidence: 98%
“…Dendrimers are three-dimensional spherical chemical structures with high monodispersity, dimensional adjustability and surface functionalization [95] , [96] , [97] , [98] . These unique features enable dendrimers to link, coordinate, or encapsulate therapeutic drugs (as shown in Fig.…”
Section: Dendrimer-based Prodrugsmentioning
confidence: 99%
“…The rapid, efficient preparation of high-generation dendrimers is important to the development of macromolecular therapeutics, diagnostic agents, catalysts, and encapsulants. Dendrimers are a particularly attractive platform for macromolecular therapeutics owing to their precisely defined molecular structure, which can be tuned at the core, interior, and periphery. However, the synthesis of monodisperse high-generation dendrimers, which are critical to many biomedical applications, remains a major challenge . Divergent dendrimer synthesis methods commonly suffer from incomplete conversion or side reactions at the dendrimer periphery, while convergent methods often suffer from poor yields or slow reaction times when high-generation dendrimers are needed.…”
Section: Introductionmentioning
confidence: 99%